Adaptive Workforce Strategies Shaping Economic Resilience in Post-Digital Transformation Era - Asnan (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2026)
The widespread digital transformation has compelled public organizations to restructure human resource management practices to maintain economic resilience. This study aims to examine the role of adaptive workforce strategies in strengthening economic resilience in the post-digital transformation era, taking the Government of Banjarbaru City as the research context. The objective of this research is to analyze the influence of adaptive strategy dimensions, including digital skills enhancement, work flexibility, and data-driven innovation, on organizational economic resilience indicators and to explain the adaptation mechanisms occurring in the workplace. The study employs a mixed-methods approach with a sequential explanatory design. In the quantitative phase, data were collected through a survey of sixty civil servants selected using purposive-stratified sampling and assessed with a Likert-scale questionnaire, while the qualitative phase involved in-depth interviews with eight key informants from strategic work units. Quantitative data were analyzed using descriptive statistics and multiple linear regression to test the strength and significance of relationships among variables, whereas qualitative data were analyzed thematically to explore contextual and adaptive patterns. The results reveal that digital skills enhancement and work flexibility have a positive and significant effect on organizational economic resilience, while data-driven innovation strengthens the effectiveness of both strategies. This study concludes that the adaptive capacity of the workforce is a crucial factor in enhancing economic resilience and contributes both theoretically and practically to the development of human resource policies in the public sector.